Fred Lesher letter to Thomas Kent regarding Wood Duck sighting, November 30, 1985 - Lesher, Fredet al (1985)
A postcard from Fred Lesher to Thomas Kent reporting Wood Ducks at Lansing and mentioning that there should be Tundra Swan at Harpers Ferry. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed/flatbed